Association Of Conjunctival Vitreous Reflux With Intraocular Pressure Spikes After Intravitreal Bevacizumab Injection - Abbasi , Kanwal Zareen; Jameel, Ameera; Khan, Muhammad Rizwan; Mirza, Bilal Humayun; Tariq, Salman; Abbasi, Muhammad Sajid Rafiq (Journal of Rawalpindi Medical College, 2024)
Objective: To evaluate the effect of conjunctival vitreous reflux on intraocular pressure immediately after intravitreal bevacizumab injection. Methods: A prospective interventional study was done at Benazir Bhutto Hospital, for 6 months from 13-01-2021 to 12-07-2021.Patients were selected through a non-probability consecutive sampling technique. A total of 88 eyes undergoing intravitreal bevacizumab were included in the study. IOP was checked before injection, immediately after injection, at 30 minutes and 60 minutes. The presence or absence of conjunctival reflux was noted. Data was analyzed to see the association of post-injection IOP and conjunctival reflux. Results: Those having conjunctival reflux positive had mean Intraocular pressure before intravitreal injection 13.14+2.569, the p-value was 0.0001. Immediately after injection at 0 minutes it was 27.95+3.988, and the p value was 0.0001. At 30 minutes, it was reduced to 21.58+2.814, the p-value was 0.0001, and at 60 minutes, the mean intraocular pressure was 17.26+1.853, and the p-value was 0.001. Those having conjunctival reflux negative had mean Intraocular pressure before intravitreal injection 13.44+2.981, p-value 0.0001. Immediately after injection at 0 minutes it was 33.69+5.608, and the p-value was 0.0001. At 30 minutes, it was reduced to 24.51+5.337, the p-value was 0.0001, and at 60 minutes, the mean intraocular pressure was 18.98+2.973, and the p-value was 0.001. Conclusion: Patients with vitreous reflux positive had less IOP elevation as compared to those with vitreous reflux negative. Keywords: Intravitreal bevacizumab injection, Intraocular pressure, conjunctival reflux.